Emotes in Mobile Legends Game Communication: A Semiotic Perspective - Sya'baan, Andi Muh. Ruum; Hasyim, Muhammad; Iman, Muhammad Nur; Rahmawati, Rahmawati; Lakuana, Nurhaida (English Education Study Program, 2024)
This research aims to determine the meaning and function of expressions using emotes in the Mobile Legends game. The object of this research is the Mobile Legends game. The research data is in the form of emotes in the game and grouped using Pierce's semiotic approach (Representation, object and interpretant), then data analysis is carried out by describing the meaning of emotes in the Mobile Legends game. The results found that there are several functions of emote markers such as expression markers of praise, ridicule, surprise /surprised, recognizing greatness, and frustration increasing enthusiasm, 'being stupid/don't care. There are several communication systems in the Mobile Legend game including: 1) Chat column feature, 2) Quick chat feature, 3) Direct conversation feature. , and 4) Emotes. Of these four features, the emote feature is most widely used in communication when playing the Mobile Legends game. This emote feature is a form of communication that combines several elements, namely images, text, movement and sound. This certainly creates a more interesting playing atmosphere.